FRI0426 EMOTIONAL COMPONENTS AND INFLAMMATION ARE HIGHLY RELEVANT IN PAIN REPORTED BY KNEE OSTEOARTHRITIC PATIENTS. (2nd June 2020) - Tío, L.; Castro, F.; Tassani, S.; Gónzález-Ballester, M. Á.; Noailly, J.; Monllau, J. C.; Monfort, J.
Abstract : Background: Osteoarthritis (OA) is a leading cause of disability in elderly and the most frequent form is knee OA (KOA) (1). Pain is the principal symptom that leads patients to visit clinicians, and it is the main reason, together with functionality, for patients to undergo a total knee replacement (TKR) after apparently unsuccessful conservative (CNV) treatments (2). It is well-known that there is a poor correlation between the radiographic severity (based on Kellgren & Lawrence (KL) score) and the reported pain (3), so other variables may be responsible for the intensity of pain. Objectives: Identifying the leading causes of pain in each patient would improve the management of the disease. In this study we aim to investigate the role of emotional components, nociception process and inflammation in treatment decision, as a global measure of pain suffered by KOA patients, taking into account sex, age and BMI. Methods: KOA patients, carefully selected to be idiopathic, graded 2-3 in KL, were recruited at Hospital del Mar. The following variables were recorded: WOMAC, Hospital Anxiety and Depression Scale (HAD), Pain Catastrophizing Scale (PCS), tender points (TP) (measure with a pressure algometer at points defined in the Arendt-Nielsen extended peripatellar map), synovial hypertrophy (SH) and effusion (SE) (measure by ultrasounds), and PCR and ESR serum levels. Patients were classified according to 4 factors: treatment (CNV/TKR), sex, age (60-67/68-75) and BMI (<30/>30). All groups were balanced. Multivariate and correlations analysis were performed. Results: Eighty-seven patients have been recruited. Patients from the TKR group present significant higher WOMAC (p=0.000), PCS (p=0.002) and SE (p= 0.038) values than CNV ones, without interaction with the other factors, except for SE, that presents interaction with BMI (Fig. 1 ). Women reported significant upper WOMAC (p=0.001) and HAD rates (p=0.020), but also higher number of TP and ESR levels (p= 0.000 and 0.002, respectively). The level of sensitization was significantly higher in women than in men (p=0.000). Several significant correlations were found, mainly between WOMAC and emotional components, as well as between TP and WOMAC, PCS, and inflammation markers (Table 1). Conclusion: PCS is an emotional component that could explain in part the lack of correlation between joint status and patient's symptomatology. Working out strategies for pain management could improve this PCS values and therefore reduce the need for TKR. Furthermore, this study also highlights the two mainly types of OA etiology: mechanical and inflammatory. It suggests that inflammation is mostly responsible for OA progression in patients with low BMI, and plays a strong role in women pathology. Finally, specific treatments targeting central pain sensitization could also improve the management of the pathology in women. References: [1]Guccione AA, Felson DT, Anderson JJ, Anthony JM, Zhang Y, Wilson PW, et al. The effects of specific medical conditions on the functional limitations of elders in the Framingham Study. Am J Public Health. 1994 Mar;84(3):351-8. [2]O'Neill TW, Felson DT. Mechanisms of Osteoarthritis (OA) Pain. Curr Osteoporos Rep. 2018 Oct;16(5):611-6. [3]Dieppe PA. Relationship between symptoms and structural change in osteoarthritis. what are the important targets for osteoarthritis therapy? J Rheumatol Suppl. 2004 Apr;70:50-3. Acknowledgments: MICINN Funds are acknowledged (HOLOA-DPI2016-80283-C2-1/2-R) Disclosure of Interests: None declared